THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL, AND MEDIUM ENTITIES (SAK EMKM) AND CALCULATION OF FINAL INCOME TAX IMPOSITION PP 23 OF 2018 IN THE FINANCIAL STATEMENT OF COFFE SHOP RUMAH KITA - Archilues, Maria Cyntia (Jurusan Akuntansi FEB UNTAN, 2025)
The existence of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia plays a significant role in Indonesia's economic growth and resilience. Along with the increasing number of MSMEs in Indonesia, the quality of MSMEs needs to be maintained for the sustainability and prosperity of Indonesia. The way to improve the quality is to prepare standardized financial statements on SAK EMKM, as well as contribute to the right tax for MSMEs. This study aims to determine the application of SAK EMKM in the financial statements of Rumah Kita Coffee Shop, as well as to calculate the final income tax of PP No. 23 of 2018. This research uses qualitative methods with a case study approach. The results showed that Rumah Kita Coffee Shop has not implemented SAK EMKM in its financial statements and has never calculated the imposition of final income tax PP No. 23 of 2018. There are obstacles faced not implementing SAK EMKM and calculating the right final income tax based on the financial statements, namely lack of knowledge and information about SAK EMKM, lack of time to learn independently to make financial statements in accordance with standards, lack of human resources and lack of socialization and training from the government and institutions related to SAK EMKM.